Studi Empiris Kepuasan Konsumen pada Masa Pandemi Covid-19 - Putri, Okta Ananda; Supeni, Retno Endah; Winahyu, Pawestri (Politeknik Negeri Jember, 2023)
The phenomenon of consumer satisfaction at Salon Wildan which includes overall satisfaction (consumer overall satisfaction after consuming services), experience satisfaction (level of satisfaction experienced by consumers while consuming services), feeling comfortable when using the service, willingness to use the service repeatedly, willingness to recommend ( willingness to recommend) consumers are not yet completely satisfied. Of the five indicators, consumers still feel dissatisfied. This is a problem regarding consumer satisfaction at Salon Wildan which requires solving and analyzing what factors can influence consumer satisfaction. The aim of this research is to test and analyze the significant influence of price, service quality and location on consumer satisfaction at Salon Wildan Banyuwangi. This type of research is exploratory and conclusive research, where conclusive research can be classified as descriptive and causality research. The population of this research is consumers of Salon Wildan Banyuwangi. The sample used was 100 respondents using purposive sampling technique. The analytical tool is multiple linear regression analysis and uses exploratory and conclusive methods. The research results prove that price, service quality and location have a significant effect on consumer satisfaction at Salon Wildan Banyuwangi. The implications of this research can be a consideration for business managers so that they can optimize pricing, service quality and location so that they can increase consumer satisfaction and the business runs well.